Most-Wanted English Learning Mobile Apps - Mokhammad Nizzam (Program Studi PGMI STAI Daruttaqwa Gresik, 2020)
Covid-19 pandemic has contributed a great encouragement for autonomous learners in using mobile learning to learn foreign languages, including English. Geared under qualitative design, the present study aims to find out the availability of mobile apps that most people use in learning English. It concerns to review and make comparisons among the top three most popular apps gathered on the Google Playstore list to investigate what they teach, how they teach, and what technology they use in order to figure out on which aspects they are distinct to each other and on which they are similar, where are they lacking, and what they do well. The results point out that the apps were developed in such easy and fun ways of learning with various materials, ie daily life situations, and stories. Though enriched with vast exercises in receptive skills, they are commonly offered limited practice in productive skills.